A knowledge-based approach to facilitate queries by hajj pilgrims - Sulaiman, Sarina; Sulaiman, Shahida; Mohamed, Hasimah; Mohd. Arshad, Muhammad Rafie; Ahmad, Anees (Faculty of Computer Science and Information System, 2008)
Hajj pilgrims need to undergo a proper and comprehensive training before leaving their mother countries in order to perform a successful and rewarding hajj. Despite of being trained, the pilgrims might not be aware of some rules and regulations that may affect their hajj rituals or rites if the pilgrims do not follow them. They may have many queries pertaining to hajj rituals, which cannot be found in their guidebooks. They could have the queries while doing any of the rituals in the middle of the crowded areas and might need to call the experts to solve the queries. However if they cannot contact the experts at the moment, they might not be able to find the solution immediately. We propose a question and answer (Q&A) expert system using a knowledge-based approach to facilitate queries by the hajj pilgrims either before or while performing their hajj rituals. We have developed the research prototype on a Web-based application, which we suggest to be installed on kiosks located around Mecca or Madinah or in handheld devices. This paper covers the theoretical aspects of knowledge-based approach to facilitate queries by hajj pilgrims. We also discuss some basic examples of how the approach can be realized in a hajj Q&A system as a personalized e-hajj guidebook